TEORI KODE-KODE BERBICARA - Pala, Rukman (Jurnal Insani, 2014)
This article substantive describes The Theory of Speaking Codes from Gerry Philipsen. Briefly, these include background birth of the theory; the substance of Speaking Code Theory; shape/appearance of ethnography; criticism of the theory; and conclusion. The discussion showed that one of the five core theory is related to the arguments stated in the form of propositions, that “where there is a cultural difference, there will be found different speaking code". From the meaning of ‘postulate referred to’ in relation to a number of example case about the working Theory of Speaking Codes in reality daily life before that, this indicates that for Indonesia this theory can actually be a confirmation and practical guidance for each individual of an Indonesian ethnic community nation in cross-cultural communication in order to make harmonization.